Analisis Kuantitatif Minyak Atsiri Dari Serai (Cymbopogon sp) Sebagai Aromaterapi - Udrika Lailatul Qodri (Tinctura, 2020)
The increasing need for essential oils is directly proportional to the development of modern industries in the fields of perfume, food, cosmetics, medicine and aroma therapy industries. Lemongrass plant has the potential to produce essential oils and can be used as aromatherapy. The purpose of this study was to quantitatively analyze the essential oil of lemongrass (Cymbopogon sp.) As aromatherapy. This research is a quantitative descriptive study, namely the extraction of lemongrass, namely the part of the stem, the material used is simplicia and the next stage is to analyze the quality of simplicia (moisture content) and the identification of essential oils (yield, organoleptic testing and specific gravity). The results showed that the water content of lemongrass simplicia was 6%, the highest yield percentage in dry samples was 0.72%. The organoleptic results showed that the essential oil of lemongrass simplicia was light yellow, had a distinctive aromatic smell, had a bitter taste and a specific gravity of 0.878 gr / ml. Keywords: Lemongrass Plant, Essential Oil, Aromatherapy ABSTRAK Peningkatan kebutuhan terhadap minyak atsiri berbanding lurus dengan perkembangan industry modern dibidang industry parfum, makanan, kosmetik, obat-obatan dan aroma terapi. Tanaman serai memiliki potensi sebagai penghasil minyak atsiri dan bisa dimanfaatkan sebagai aromaterapi. Tujuan dari penelitian ini untuk menganalisa secara kuanitatif minyak atsiri dari tanaman serai (Cymbopogon sp.) sebagai aromaterapi. Penelitian ini termasuk penelitian deskriptif kuantitatif yaitu ekstraksi tanaman serai yaitu bagian batang, bahan yang digunakan adalah simplisia dan tahapan selanjutnya menganalisa mutu simplisia (kadar air) dan identifikasi minyak atsiri (rendemen, ujiorganoleptik dan bobot jenis). Hasil penelitian menunjukkan kadar air simplisia serai sebesar 6%, Presentase rendemen yang paling tinggi pada sampel kering yaitu 0.72%. Hasil organoleptik menunjukkan minyak atsiri dari simplisia serai berwarna kuning muda, berbau khas aromatic, rasa pahit dan bobot jenis 0.878 gr/ml. Kata Kunci: Tanaman Serai, Minyak Atsiri, Aromaterapi